Efficacy of a herbal toothpaste on patients with established gingivitis: a randomized controlled trial Eficácia de um dentifrício fitoterápico em pacientes com gengivite estabelecida: ensaio clínico aleatório - Fabiana Ozaki; Claudio Mendes Pannuti; Ana Vitória Imbronito; Wellington Pessotti; Luciana Saraiva; Nívea Maria de Freitas; Graziella Ferrari; Veronica Neto Cabral (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The aim of this randomised, double blind controlled trial was to verify the efficacy of a herbal dentifrice on the reduction of plaque and gingivitis. Forty eight volunteers with established gingivitis were randomly assigned to either a test group (herbal dentifrice) or positive control group (dentifrice with triclosan and fluoride). The dentifrices were distributed in plain white tubes by an independent pharmacy, which revealed the contents of each tube only after the experimental period. Plaque and gingivitis assessments were carried out on baseline and after 28 days of product use. All examinations were conducted by the same calibrated investigator. Subjects were instructed to brush their teeth three times daily using their assigned dentifrice for 28 days. There was a significant reduction in plaque levels in both the test and control groups. However, there was no significant difference between the groups. A significant reduction in gingivitis was observed in both groups, although there was no significant difference between them. No adverse reactions were reported. The authors concluded that both dentifrices were effective in reducing plaque and gingivitis in subjects with established gingivitis. O objetivo deste ensaio clínico aleatório duplo-cego foi verificar a eficácia de um dentifrício fitoterápico na redução de placa e gengivite. Quarenta e oito voluntários com gengivite estabelecida foram aleatoriamente alocados aos grupos teste (dentifrício fitoterápico) e controle positivo (dentifrício com triclosan e flúor). Os dentifrícios foram distribuídos em tubos brancos por uma farmácia independente, que revelou o conteúdo de cada tubo apenas após o final do período experimental. A aferição de placa e gengivite foi conduzida por um único examinador, previamente calibrado, no início e após 28 dias de uso do produto. Os sujeitos da pesquisa foram orientados a escovar os dentes com o dentifrício de seu grupo três vezes ao dia, por 28 dias. Houve redução significativa na quantidade de placa nos grupos teste e controle. No entanto, não houve diferença significativa entre os grupos. Os dois grupos experimentais apresentaram redução significativa nos níveis de gengivite, porém não houve diferença significativa entre eles. Não foram observadas reações adversas. Os autores concluíram que os dois dentifrícios foram eficazes na redução de placa e gengivite em indivíduos com gengivite estabelecida.